Repeated evolution of digital adhesion in geckos: a reply to Harrington and Reeder. (18th May 2017) - Gamble, T.; Greenbaum, E.; Jackman, T. R.; Russell, A. P.; Bauer, A. M.
Abstract: We published a phylogenetic comparative analysis that found geckos had gained and lost adhesive toepads multiple times over their long evolutionary history (Gamble et al ., PLoS One, 7, 2012, e39429). This was consistent with decades of morphological studies showing geckos had evolved adhesive toepads on multiple occasions and that the morphology of geckos with ancestrally padless digits can be distinguished from secondarily padless forms. Recently, Harrington & Reeder ( J. Evol. Biol., 30, 2017, 313) reanalysed data from Gamble et al. (PLoS One, 7, 2012, e39429) and found little support for the multiple origins hypothesis. Here, we argue that Harrington and Reeder failed to take morphological evidence into account when devising ancestral state reconstruction models and that these biologically unrealistic models led to erroneous conclusions about the evolution of adhesive toepads in geckos.